Successful Gardening : In Warm Climates - McFarlane, Annette (Melbourne Kangaroo Press)
Completely updated, this classic title includes more than 150 photographs and is an essential reference for Australian gardeners.
Include Color Illustration and Index
Keywords: Australia -- Gardening -- Organic gardening